Prayer : Does it make any difference? - Yancey, Philip (Zondervan, 2006)
Philip Yancey probes the very heartbeat of our relationship with God: prayer. What is prayer? Does it change God's mind or ours or both? This book is an invitation to communicate with God the Father who invites us into an eternal partnership through prayer.